Incidence of ascites on different genetic categories of broilers fed with high-energy diet - Neto, Manoel Garcia; Campos, Egladson João (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to verify the incidence of ascites on grand parents, breeders and commercial broilers from the same genetic strain of birds, fed with high energy level ration, from the first day of age to 39 days old. All birds were grown as commercial broilers receiving a ration ad libitum with 3,050 kcal/ME; birds from female line, male line and commercial broilers were tested. A total of 2,700 birds were housed at random in a experimental facility of 8x76 m, with 27 compartments of 3x3.5 m each and 100 birds per division. A factorial design was used with three replications per treatment. The incidence of ascites was not dependent on genetic category.
Keywords: inbred lines; metabolic disorders; genetic parameters; animal nutrition